Narratives of Italian Transatlantic (re)migration, 1897–1936 - Viola, Lorella (Frontiers in Sociology, 2023)
According to historical statistics, Italians were one of the groups most actively engaged in Transatlantic remigration; however, more recent readings show that many of these returnees eventually reemigrated to the US. This study offers a novel and intimate perspective on remigration that investigates the reasons for a failed resettlement in Italy. Using for the first time immigrant newspapers as a source, the article integrates quantitative and qualitative methods to analyse Italian migrants' own accounts of remigration against the context of the national debate of emigration and remigration. The results will show a discrepancy between the Italian public discourse which praised remigration as positive for the country, both economically and socially, and Italian Americans' personal accounts which were more complex and ambivalent. The article will argue that such contrast is the visible outward sign of a much more profound issue: the Italian Government's view of (r)emigration -mainly through the lens of domestic economic advantage -deeply underestimated the complexity of migration as a social phenomenon and as a profoundly changing psychological experience. In the long run, this error of judgement deeply damaged Italy as many of those ritornati felt misunderstood and disillusioned and crossed the Atlantic again, this time never to return.